COVID-19 Promotion and Prevention Measures in the Fish Auction in Karan Aur Pariaman City - Aprihatin, Yessy (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The purpose of this research is to explain the COVID-19 promotive and preventive action in the neighbourhood of fish auction in Karan Aur Village Pariaman City. This method of study uses a descriptive technique, which explains how promotive and preventive efforts are performed in the field. Promotive action about the COVID-19 conducted in the fish auction in the town of Pariaman in the form of counselling in the community. This indication is seen from the community enthusiastic in the question and when the feedback about the disease COVID-19, the community's ability to answer questions also has begun well. As for the constraints in conducting counselling are also found as there are still people who do not concentrate in following the counselling caused because of their attention is distracted by children who are also brought at the time of counselling. Counselling time it felt too short, so the delivery of the extension material is not optimal. COVID-19 preventive execution generally runs as planned. While making preventive measures, there are still many people who do not behave well in the prevention of the spread of Coronaviruses, such as not keeping the distance at the time of communication, the presence of gatherings of people who are more than 5 people without wearing masks. At the time of giving counselling to the shop owner/crotch in the fish auction place about the importance of providing water and soap for hand wash ready action. In general, the shop/shop will apply the action, but there are also found shops/stalls that do not heed this preventative effort.